Selection of compression test images using variance-based statistical method - Chems El Houda Allaoui; Abdesselam Bassou; Ismahane Benyahia; Mustapha Khelifi (Institute of Advanced Engineering and Science, 2019)
In this research paper, we used a variance-based statistical method to select 20 test images, according to these latter types (natural, satellite and medical) among a sample of 300 images (100 natural, 100 satellite and 100 medical). The images selection has been done using parameters of image quality, namely PSNR, MSSIM and VIF, which were applied on three compression algorithms (DWT+SPIHT, JPEG, and JPEG2000).